LEADERSHIP CHALLENGES IN HUMAN RESOURCE MANAGEMENT: A COMPARATIVE ANALYSIS OF PAST AND CONTEMPORARY ERAS - Omar Ashurbayev (The latest news and research in education, 2025)
The trajectory of Human Resource Management (HRM) from its embryonic stages in the early twentieth century to its current strategic centrality represents a profound metamorphosis in organizational governance. At the heart of this transformation lies the evolving nature of leadership within HRM, which has transitioned from predominantly administrative and transactional responsibilities to strategic business partnership (Wright and Ulrich, 2017). This article undertakes a comprehensive comparative examination of leadership challenges confronting HRM professionals across distinct historical epochs, with particular attention to juxtaposing past challenges (1960s-1990s) against contemporary issues (2020s). Such analysis yields critical insights for practitioners and scholars navigating the increasingly complex terrain of human capital management.